THE INFLUENCE OF SOCIAL MEDIA ON ADOLESCENT MENTAL HEALTH: A LITERATURE REVIEW - Anissa, Mutiara; Lovprima, Nopeliantesa; Septiani, Vadila; Abdullah, Dessy; Hasni, Dita (Journal of Psychology, 2024)
Introduction/ Background: Based on WHO data, as many as 10-20% of children and adolescents in the world experience mental health problems. It is estimated that 50% of mental disorders occur by the age of 14 and 75% by the age of 18. The most common disorders in children and adolescents are generalized anxiety disorder and depression. Social media users in Indonesia reach 150 million (56%) of the total population. In Indonesia, teenagers are the most popular social media users. The impact received from the influence of social media is the disruption of mental health, such as depression caused by cyberbullying. Objective: This study aims to analyze social media's influence on adolescent mental health—method: Method used in the narrative review with PRISMA 2020. The literature search in this literature review uses two databases: Google Scholar and ScienceDirect. The critical words of the Indonesian Language are the influence of social media and adolescent mental health. English keywords are social media influence and adolescent mental health. Results: The results of a study from 11 journals found that mental health problems owned by adolescents who use social media include emotional mental disorders, abnormal emotional symptoms, abnormal behavior problems, abnormal hyperactivity, and abnormal peer problems. Adolescent mental health problems mainly occur in adolescent girls. Based on the results of all studies, social media influences mental health problems experienced by adolescents. Conclusion: Social media is used by almost everyone in this world today. The majority of social media use is by teenagers. Social media hurts adolescent mental health. Teenagers must use social media wisely.